Threat Assessments from Fires and Torrential Floods: Case Study Experience - Camargo, Carlos Andrés Caro; Villate, Julián; Garavito, Laura (Threat Assessments from Fires and Torrential Floods: Case Study Experience, 2024)
Climate change and extreme phenomena in the world have been causing countless human and material losses, which has led different governments to take action measures to mitigate and prevent possible natural disasters, from the generation of infrastructure to the creation of laws or guidelines that help normalize processes and action schemes. Specifically in Colombia, and as a consequence of the girl phenomenon that occurred in 2010 and 2011, the risk management law was created by the Congress of the Republic in 2012. This law has obliged the different construction sectors to accommodate new demands and depending on the different types of risks, depending on the type of work to be executed or designed. In this book, a guide is presented to determine the threats from fires and torrential floods that may occur in a typical Colombian basin, taking as reference a specific case study.